1970
DOI: 10.3329/bjar.v33i4.2290
|View full text |Cite
|
Sign up to set email alerts
|

Microspore culture and the performance of microspore derived doubled haploid in <i>Brassica juncea</i> (L.)

Abstract: The experiment was conducted at the Tissue Culture Laboratory as well as in the net house of Oilseed Research Centre, Bangladesh Agricultural Research Institute (BARI), Joydebpur, Gazipur on microspore culture and the performance of microspore derived doubled haploid (DH) in Brassica juncea (L.). The variety BARI Sarisha II of B. junccea was used for microspore culture and 8 DH genotypes viz., BJDH 01, BJDH 05, BJDH ii, BJDH 12, BJDH 14, BJDH 17, BJDH 18, and BJDH 20 along with their parent Rajat collected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The optimal size for B. juncea cv. 'BARI Sarisha 11' was 3.0-3.1 mm (Ali et al 2008), or 3.1-3.5 mm in cv. 'Varuna' (Prem et al 2008).…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…The optimal size for B. juncea cv. 'BARI Sarisha 11' was 3.0-3.1 mm (Ali et al 2008), or 3.1-3.5 mm in cv. 'Varuna' (Prem et al 2008).…”
Section: Discussionmentioning
confidence: 96%
“…bud length) and developmental stage of immature pollen grains: most microspores at the late-uninucleate to early binucleate stage can undergo embryogenesis (Pechan and Keller 1988;Hansen and Svinnset 1993;Custers 2003;Prem et al 2005;Abraha et al 2008). The high response of microspore Zaki and Dickinson (1995) B. campestris Canadian Cv-2 5390 embryos/100 buds nr nr Guo and Pulli (1996) B. juncea Couve Algarvia 9 embryos/2 buds nr nr Dias and Correia (2002) B. juncea Rajat 3500 embryos/100 buds 52 nr Chanana et al (2005) Interspecific hybrid of B. napus L 365 embryos/3 buds nr nr Smýkalová et al (2006) HSH nr not reported, a under optimal conditions embryogenesis in the same developmental stage was also recorded in B. campestris (Guo and Pulli 1996), B. carinata (Abraha et al 2008), B. juncea (Chanana et al 2005;Agarwal et al 2006;Ali et al 2008;Prem et al 2008), B. napus cv. 'Topas' (Anandarajah et al 1991;Takahata and Keller 1991;Supena et al 2006), and B. oleracea var.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations